Giant days - Allison, John, 1976-; Treiman, Lissa; Cogar, Whitney; Campbell, Jim (Letterer) (Los Angeles, CA : Boom! Studios, 2015)
"Susan, Esther, and Daisy started at university three weeks ago and became fast friends. Now, away from home for the first time, all three want to reinvent themselves. But in the face of hand-wringing boys, "personal experimentation," influenza, mystery-mold, nu-chauvinism, and the willful, unwanted intrusion of "academia," they may be lucky just to make it to spring alive. Going off to university is always a time of change and growth, but for Esther, Susan, and Daisy, things are about to get a little weird."--provided from Amazon.com.
Keywords: Teenage girls -- Comic books, strips, etc; Women college students -- Comic books, strips, etc; Female friendship -- Comic books, strips, etc; Comics (Graphic works) -- Great Britain; Graphic novels; Comics (Graphic works)